2019
DOI: 10.1007/s00167-019-05415-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for 30-day readmission following hip arthroscopy

Abstract: Purpose Hip arthroscopy is known to be safe with low rates of postoperative complications. The purpose of this study is to evaluate hip arthroscopy cases in a national surgical database to identify risk factors associated with readmission. Methods The American College of Surgeons National Surgical Quality Improvement Program database was queried from 2012 to 2016 for current procedural terminology billing codes related to hip arthroscopy. International Classification of Diseases diagnostic codes were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
2
13
3
Order By: Relevance
“…They did not report on the readmission rate. Hartwell et al 7 seem to have covered a similar period as the current study from 2012 to 2016 in their publication earlier this year and reported a slightly greater readmission rate of 1.3% in a group of 1493 patients. They identified bleeding (n ¼ 12, 0.8%), superficial infection (n ¼ 5, 0.3%), and return to operating room (n ¼ 4, 0.3%) as the most common events.…”
Section: See Related Article On Page 3271supporting
confidence: 71%
See 2 more Smart Citations
“…They did not report on the readmission rate. Hartwell et al 7 seem to have covered a similar period as the current study from 2012 to 2016 in their publication earlier this year and reported a slightly greater readmission rate of 1.3% in a group of 1493 patients. They identified bleeding (n ¼ 12, 0.8%), superficial infection (n ¼ 5, 0.3%), and return to operating room (n ¼ 4, 0.3%) as the most common events.…”
Section: See Related Article On Page 3271supporting
confidence: 71%
“…There are a couple of limitations of the study that need to be highlighted, one being its similarity to the work by Hartwell et al 7 using the same database; unsurprisingly, the conclusions are not very different. It must be admitted that the focus of the study by Hartwell et al 7 was the 30-day complication rate and they attempted to determine its association with several surgical factors; in contrast, the current study has explored the medical associations at length and the authors should be congratulated for their attempt. It can also be critiqued that for a study including data from 693 participating hospitals, one would expect a larger cohort of patients, which is perhaps even more valuable if the incidence of the complications is very small.…”
Section: See Related Article On Page 3271mentioning
confidence: 75%
See 1 more Smart Citation
“… 2 , 3 , 13 , 20 , 27 Chronic systemic steroid use has also been associated with significantly increased complication rates after arthroscopy. 9 , 31 Westermann et al 31 noted a 3-fold increased rate of readmission because of surgical-site infection and wound complications in patients with chronic steroid use who had knee and shoulder arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have identified low 30-day readmission rates (0.5%-1.3%) following hip arthroscopy; however, as this study suggests, this may underestimate the rate at which these patients seek outpatient medical attention. 2,5 They identified a 30-day postoperative emergency department evaluation rate of 3.5% along with a 0.13% 30-day readmission rate. The current study provides unique and valuable information regarding the postoperative complications that lead patients to seek medical care after hip arthroscopy.…”
Section: See Related Article On Page 1575mentioning
confidence: 99%